Exploring the creative process of the collaborative artwork “painting in dance”: an autoethnographic study - Fadhlan, Fadhlan; Guntur, Guntur; Sunarmi, Sunarmi (International Journal of Visual and Performing Arts, 2025)
This study explores the creative process of the collaborative artwork Painting in Dance, which merges dance and painting through an innovative, real-time interaction between a dancer and a painter. Employing an art-based autoethnographic approach, the research documents personal experiences and reflections to reveal how spontaneous movement and Action Painting techniques inform each other. Data were collected through visual documentation, self-interviews, and personal journals, and analyzed thematically and narratively. The findings identify four key stages of collaborative creativity: exploratory contemplation, improvisation, expressive collaboration, and final touches. These stages transform the dancer’s body into an active medium for painting. This study contributes a novel model of interdisciplinary artistic creation, demonstrating how integrating dance and visual art can produce dynamic, multisensory performances and inspire new pedagogical approaches in contemporary art education.